2016
DOI: 10.4149/gpb_2016011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to extremely low-frequency electromagnetic fields on the differentiation of Th17 T cells and regulatory T cells

Abstract: Abstract. The potential risks that electromagnetic fields (EMF) pose to human physiology have been debated for several decades, especially considering that EMF is almost omnipresent and some occupations involve regular exposure to particularly strong fields. In the present study, the effects of 60 Hz 0.3 mT EMF on CD4 + T cells were evaluated. Production of T cell related cytokines, IFN-γ and IL-2, was not altered in CD4 + T cells that were exposed to EMF, and cell proliferation was also unaffected. The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…4B). The differentiation of Th17 and Treg cells is mediated by downstream regulator STAT3 and STAT5 respectively (23). As expected, the expression of STAT3 was substantially increased and STAT5 was obviously decreased in splenic lymphocytes of TAC mice.…”
Section: The Effect Of Egcg On the Expressions Of Regulators Forsupporting
confidence: 64%
See 1 more Smart Citation
“…4B). The differentiation of Th17 and Treg cells is mediated by downstream regulator STAT3 and STAT5 respectively (23). As expected, the expression of STAT3 was substantially increased and STAT5 was obviously decreased in splenic lymphocytes of TAC mice.…”
Section: The Effect Of Egcg On the Expressions Of Regulators Forsupporting
confidence: 64%
“…EGCG, Epigallocatechin gallate; TAC, transverse aortic constriction; Val, valsartan.naive Th cells, and exert opposite functions. The differentiation of Th17 depends on the activation of STAT3, while the development of Treg is mediated by the activation of STAT5(23). The imbalance of Th17/Treg is an important feature of inflammation and autoimmune diseases(33).…”
mentioning
confidence: 99%
“…Developmental pathways of Th17 and Treg cells are closely related. TGF-β alone induces expression of FoxP3 (30,31) and RORγT (31) in TCR-stimulated naive CD4 + T cells. Thus TGF-β is a critical factor for Th17 and Treg cells and is essential for inducing both RORγT and Foxp3.…”
Section: Cellular and Molecular Mechanisms Of Mdscmediated Immune Supmentioning
confidence: 99%
“…It was also found that ELF‐EMFs affected the expression of CD4, CD14, and CD16 [Conti et al, ]. Another study confirmed that ELF‐EMFs had effects on Th17 and Treg cells [Lee et al, ]. However, the Th9 subset is a recently‐discovered T helper cell subset and has not yet been studied extensively.…”
Section: Discussionmentioning
confidence: 99%
“…Each coil was made of 200 turns of 1‐mm diameter insulated soft copper wire and was connected in series to a 220‐V alternating current power supply via a transformer. Details of the methods were described in our previous study [Lee et al, ; Kim et al, ].…”
Section: Methodsmentioning
confidence: 99%